Evolution of solid waste management in Malaysia: impacts and implications of the solid waste bill, 2007 - Agamuthu, Pariatamby; Khidzir, K.; Hamid, F.S. (2009)
Solid waste generation and its implications for people and the environment are global issues. The complexity of the waste composition and the ever-increasing percapita waste generation is a challenge for waste managers, particularly in developing countries. Thus, the need to have a clear policy on waste management and legislation to realize that policy is imperative. Malaysia is developing rapidly and problems such as the waste generation associated with development and industrialization are evident. The Solid Waste and Public Cleansing Management Bill, which was approved in August 2007 after a 10-year delay, is envisaged to have serious consequences in waste management practices and implementation in Malaysia. This article explores the main features of this all-encompassing bill and its impacts on the waste management scenario in Malaysia. In addition, a comparative evaluation is also discussed to explore the policies/legislation of selected countries vis-A vis the Malaysian bill.